Teratoma of the Neck on Fine Needle Aspiration Cytology: An Unusual Case Presentation - Sukumar, Challa; Jahan, Aarzoo; Yadav, Shakti Kumar; Singh, Sompal; Sarin, Namrata (Annals of Pathology and Laboratory Medicine, 2021)
Teratomas are tumours which are derived from all the 3 germ cell layers: endoderm, mesoderm and ectoderm with varying proportions. Cervical teratomas in children are almost always benign but locally aggressive. They can present with respiratory distress and immediate excision is required. The cervical teratoma is an uncommon entity which are rarely reported in Indian medical literature particularly on FNA. We present a case of an anterior cervical teratoma in an infant which was diagnosed on the base of FNA material.